Densidad de siembra y crecimiento de maices forrajeros - Sanchez Hernandez, M.A.=700 1 Aguilar Martinez, C.U.; Valenzuela Jimenez, N.; Sanchez Hernandez, C.; Jimenez Rojas, M.C.; Villanueva Verduzco, C.
(Es, En)
Ilus., 55 ref.
Keywords: ZEA MAYS; HIBRIDOS; INDICE DE SUPERFICIE FOLIAR; COSTA RICA; AGRONOMIA MESOAMERICANA